Analisis Gaya Bahasa Tokoh Utama Perempuan dalam Novel Mariposa Karya Luluk HF - Ajeng Sukma Sumili; Althea Khairunnisaa (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This research aims to determine the types of language styles used by the main female character in the novel "Mariposa" by Luluk HF and to analyze the meaning and function of these language styles in building character characterization. The problem that will be raised in this research is the form and variations of language styles that appear in the dialogue and monologue of the main character, as well as the role of these language styles in revealing the psychological dimensions of the character. The method used is a qualitative descriptive method with a stylistic approach, where data is collected through reading and note-taking techniques for quotations that contain language styles in the novel. The results of the analysis show that there are five dominant language styles used by the main character, namely metaphor, hyperbole, personification, simile, and repetition. This language style functions to describe the character's feelings, strengthen the delivery of the message, and build an atmosphere in the story. This research has the potential to become a reference for the development of stylistic studies of contemporary Indonesian literature and can be used as learning material for stylistic analysis at the tertiary level as well as for similar research with a focus on other linguistic aspects.